Altered Venous Blood Nitric Oxide Levels at Depth and Related Bubble Formation During Scuba Diving - Cialoni, Danilo; Brizzolari, Andrea; Samaja, Michele; Pieri, Massimo; Marroni, Alessandro (Frontiers in Physiology, 2019)
Introduction Nitric Oxide (NO) plays an important role in the physiology and pathophysiology of diving, and the related endothelial dysfunction and oxidative stress roles have been extensively investigated. However most available data have been obtained before and after the dive, whilst, as far as we know, no data is available about what happens during the water immersion phase of dive. The scope of this study is to investigate the Nitrate and Nitrite (NOX) concentration and the total plasma antioxidant capacity (TAC) before, during and after a single SCUBA dive in healthy scuba diving volunteers, as well as to look for evidence of a possible relationship with venous gas bubble formation. Material and Methods Plasma, obtained from blood of 15 expert SCUBA divers, 13 male and 2 female, was investigated for differences in NOX and TAC values in different dive times. Differences in NOX and TAC values in subjects previously known as “bubble resistant” (Non Bubblers - NB) and “bubble prone” (Bubblers - B) were investigated. Results We found a statistically significant increase of NOX plasma concentration in the “bottom blood draw” and in the “safety stop blood draw” as compared to the basal pre diving condition. We did not find any difference in NOX plasma concentration between the basal value and the post diving samples. We did not find any significant statistical difference in TAC in the bottom blood sample, while the safety-stop and the post-dive samples showed higher TAC values compared with the basal value We did not find any difference in NOX and TAC mean values between Non-Bubblers and Bubblers. Discussion Our protocol, by including underwater blood drawing, allowed to monitor plasma NOX changes occurred during diving activity, and not only by comparing pre and post diving values. It is particularly interesting to note that the increased NOX values found at the bottom and at the safety stop were not observed at post dive sampling (T0, T30, T60), showing a very rapid return to the pre-dive values. In this preliminary study we did not find any relationship between bubble formation and changes in NOX parameters and TAC response.